EFEKTIFITAS FERMENTASI DAUN SELADA (LACTUCA SATIVA) SEBAGAI ALTERNATIF BAHAN PENGAWET ALAMI DAGING AYAM - Rivolta G.M. Walalangi (Jurnal GIZIDO, 2013)
Chicken meat is poultry meat has high nutritional value. Meat chickens are easily damagedby physical impact or microbial activity, requiring precise handling that chicken can bestored longer. Ensuring the quality and safety of chicken meat plays an important role forthe safety and health of consumers. Chain of technical, operational and management affectthe quality of meat produced. Microbiological contaminants is one cause of reduced qualityof chicken meat even be unsafe for consumption. Microbial contamination or spoilagepathogens causing protein degradation is the breakdown of proteins into simpler moleculessuch as amino acids that causes cells to become damaged or rotten meat.Research carried on in the laboratory of Food Microbiology Department of Nutritionpolytechnic Kemenkes Manado, June to September 2012. Design research is anexperimental laboratory with organoleptic and microbiological tests.The results showed that lettuce effective solution to inhibit microbial growth in chicken meatspoilage or damage. However, in contrast to organoleptic tests where the results indicatethe presence of irregularities in terms of aroma, color and texture. It can be concluded thatan effective solution to a long fermentation lettuce shelf life, but are less effectivepreservative used as an alternative in terms of color, flavor and texture of chicken meat. Asa suggestion this research can still be continued in other foodstuffs that require alternativenatural preservative.